Social Learning from Co-creation: Cities on an environmental mission - van Dis, Renée; Matt, Mireille; Lhoste, Evelyne; Bundgaard, Lasse; Loconto, Allison Marie (The International Journal of Sociology of Agriculture and Food, 2023)
In innovation studies, and particularly those dedicated to agricultural and environmental innovations, there has been a robust stream of research focused on understanding how multi-stakeholder groups learn from their experiences in order to implement and scale-up system innovations. This stream of research has been referred to as social learning and has focused on how groups of multiple stakeholders are able to move system innovations from protected niches into broader scale application within society. Social learning scholars mention the importance of reflexivity when learning contexts are characterised by diverse values, interests and knowledge, such as is found in co-creation processes that include actors from the quadruple helix. Other scholars argue that while the learning process itself is important, it is insufficient for transformational change – particularly when the desired change is at the societal level. A vision of actors from the quadruple helix as givers of meaning to problems, new technologies, social innovations and potential societal impact is thus required. In this short commentary, we reflect upon the linkages between visions, problem formulation and social learning when co-creation is used as a means to stimulate collective work among multiple stakeholders. We reflect upon the promises and the limits of co-creation, and the social learning that it catalyses, in the context of environmental missions.